Peran Katekese dalam Keluarga untuk Merespons Perubahan Sosial, Teknologi dan Krisis Moral - Marta Hotnauli Sirumapea; Intan Sakti Pius X (International Forum of Researchers and Lecturers, 2024)
This article discusses the role of catechesis and family dynamics in dealing with the complex dynamics of the contemporary era characterized by social change, technological advances, and moral crises. Social change poses new challenges in family structures and norms, requiring catechesis to align its guidelines with modern family realities. Meanwhile, technological progress requires the adaptation of catechesis to take advantage of new media without losing the essence of spiritual values. The moral crisis engulfing society reinforces the need for catechesis that can provide relevant ethical guidance. Family dynamics, as the basis of religious education, take center stage in understanding how catechesis can support the formation of character and moral values in the family environment. Collaboration between church and family was identified as a key element in ensuring holistic and effective religious education. Through this article, it is hoped that a deeper understanding of how catechesis can respond to changing times and remain relevant in forming the foundations of faith and morals in the contemporary family.